2014
DOI: 10.1055/s-0034-1387165
|View full text |Cite
|
Sign up to set email alerts
|

Ambient Noise in Emergency Rooms and Its Health Hazards

Abstract: Introduction The occupational risk due to high levels of noise in the hospital environment has been recognized, and the National Agency of Sanitary Surveillance of the Ministry of Health recommends evaluation and control of noise in hospital areas. Objectives To assess the sound environment in the emergency ward of a general trauma reference hospital in the city of Curitiba, Parana State, Brazil. Methods In this descriptive study, noise levels were assessed on mornings, afternoons, and evenings using an integr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 13 publications
3
19
0
Order By: Relevance
“…The fact that calls attention is that only 2.63% of the NA and 14.29% among the AD considered the environment as not noisy ( Table 1). These answers matched noise levels assessed at an ER, which ranged from 56.6 to 119 dB(A) (16,18) . Importantly, the comfort levels recommended for hospitals, according to the NBR 101522 (13) , are from 35 dB (A) to 45 dB (A).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The fact that calls attention is that only 2.63% of the NA and 14.29% among the AD considered the environment as not noisy ( Table 1). These answers matched noise levels assessed at an ER, which ranged from 56.6 to 119 dB(A) (16,18) . Importantly, the comfort levels recommended for hospitals, according to the NBR 101522 (13) , are from 35 dB (A) to 45 dB (A).…”
Section: Discussionmentioning
confidence: 77%
“…The lowest noise level was measured in the suture room (56.6 dBA), in the morning, and the highest level was the helicopter at the moment of its landing and stay (119 dBA). Among the equipment, the highest noise was the plaster saw at work (90.0 dBA), and the lowest noise was the oximeter at work (61.0 dBA) (16,18) . Measurements were held in ten internal sites in the emergency room every two minutes and thirty seconds in each site, repeated for over three times, thus four measurements were carried out in each site, maximum, minimum and equivalent continuous noise (Leq), in the morning, afternoon and evening/night (16,18) .…”
Section: Methodsmentioning
confidence: 99%
“…It is characterized by intensity (decibels), type (continuous, intermittent, variable), duration of exposure (time), and frequency (56). Research has shown that nurses in emergency clinical units are exposed to continuous ambient noise of more than 65 dB, which exceeds the maximum noise levels recommended by the WHO for hospitals (58)(59)(60). In our study, noise will be considered as a distractor and inserted directly in clinical vignettes.…”
Section: Theoretical Frameworkmentioning
confidence: 98%
“…It is characterised by intensity (decibels), type (continuous, intermittent, variable), duration of exposure (time), and frequency (70). Nurses in emergency clinical units have been shown to be exposed to continuous ambient noise of more than 65 dB, which exceeds the maximum noise levels (35) recommended by the WHO for hospitals (71,72). In our study, noise will be considered as a distractor and inserted in the proposed SG.…”
Section: Theoretical Frameworkmentioning
confidence: 99%